Implementing of HIV/AIDS Cadre Partnership to Reduce Stigma on People Living with HIV/AIDS: A Case Study - Ernawati Ernawati; Siti Aminah; Nurhayati Nurhayati; Ahmad Fathurohman (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
The performance of HIV/AIDS cadres playing a role in the wider community is still low. The capacity of cadres needs to be improved through partnerships with stakeholders. The purpose is to explain the implementation of the partnership of HIV/AIDS cadre with stakeholders as an effort to reduce stigma among people living with HIV/AIDS in Kudus Regency, Central Java Province, Indonesia. The research method used a holistic multiple-case design, with a focus on PLWHA and HIV/AIDS cadres in two locations are Kandangmas and Rejosari villages, Dawe sub-district, Kudus district. A total of 40 participants were recruited through purposive sampling with inclusion criteria. Data analysis using thematic and document analysis. The results showed that after training HIV/AIDS cadres felt more empowered, knew their roles and carried out partnerships with stakeholders. The partnership strategy addresses the critical challenges of health human resources in this region. HIV/AIDS cadres with their transformative role have the potential to improve services in the community to reduce the stigma of PLWHA so as to achieve the goal of HIV elimination.